Constraints and autonomy for creativity in extracurricular gamejams and curricular assessment - Simon Grey; David Parker; Neil Gordon (Association for Learning Technology, 2018)
The engagement observed by the players of the games that they play is a desirable quality that has not gone unnoticed in the field of education, leading to concepts such as gamification of education, game-based learning and serious games for training. Game designer Sid Meier is often cited as defining games as being 'a series of interesting decisions'. The concept of choice implies an autonomous selection from a constrained set of options. This article reflects on the impact of autonomy and constraints, and extrinsic and intrinsic motivators on students' software development work during both curricular and extracurricular activities. Finally, a model for the design of games for game-based learning is proposed in terms of autonomy and constraints with respect to learning outcomes.